Molluscs collected with otter trawl in the northern Alboran Sea: main assemblages, spatial distribution and environmental linkage - CIÉRCOLES, CRISTINA; GARCÍA-RUIZ, CRISTINA; GONZÁLEZ AGUILAR, MARIA; ORTIZ DE URBINA GUTIERREZ, JOSÉ M.; LÓPEZ-GONZÁLEZ, NIEVES MARIA; URRA RECUERO, JAVIER; RUEDA RUIZ, JOSE LUIS (Mediterranean Marine Science, 2018)
Molluscan assemblages of circalittoral and bathyal soft bottoms of the northern Alboran Sea were studied using an experimental otter trawl. Samples of fauna were collected from 190 hauls during four MEDITS surveys carried out in spring between 2012 and 2015 at depths ranging from 30 to 800 m. Measurements of water column variables (temperature and salinity) and sediment samples were taken in the same locations where faunistic sampling was carried out. A total of 101 species grouped in 55 families were recorded. Cephalopods were the most abundant group, with Abralia veranyi dominating in abundance, Octopus vulgaris in biomass and Illex coindetii and Todarodes sagittatus being the most frequently collected species. Multivariate analyses carried out separately with abundance data of demersal species, benthic species, bivalves, gastropods and cephalopods as well as of all molluscs, generally resulted in three main molluscan assemblages corresponding to a shelf assemblage (30-200 m depth), an upper slope assemblage (201-350 m depth), and a middle slope assemblage (351-800 m depth). PERMANOVA test revealed that significant differences of different groups of molluscs in relation to depth were more acute than to geographical sectors of the Alboran Sea (eastern, central, eastern and insular sectors). Abundance, biomass and species richness decreased with depth with a clear dominance of cephalopods in the slope. Significant geographical differences were mainly detected for demersal and benthic species as well as for gastropods and cephalopods between the insular sector (Alboran Island) and the western and eastern continental sectors. Both depth and temperature were the most influencing variables in the different CCA analyses using datasets of molluscs with different life styles and from different classes, but sedimentological variables displayed a more acute significant relationship with the benthic molluscs than with the demersal ones.